Identification of the Components of Standardizing School Principals’ Duties for Presenting an Appropriate Model - Mirzabigi, Sirous; Sharifi, Saber; Eslampanah, Maryam; Faraji, Anahita (Assessment and Practice in Educational Sciences, 2026)
ABSTRACTThe present study aimed to identify the components of standardizing school principals’ duties in order to propose an appropriate model. This study was fundamental in nature and conducted using a qualitative approach. The research tradition employed was Grounded Theory. The statistical population consisted of academic experts, including faculty members holding doctoral degrees and possessing more than 10 years of teaching experience, who were selected through purposive sampling. The researcher achieved theoretical saturation after conducting interviews with 16 experts. In addition to the library research method, semi-structured interviews were used to collect data. Data analysis was carried out using the grounded theory approach. The findings indicated that identifying and analyzing the different dimensions of the standardized model of school duties requires simultaneous attention to causal, contextual, intervening, and strategic factors. Causal conditions include factors that directly influence the formation and performance of schools and provide the necessary foundation for designing and implementing standardized duties. The central phenomenon of the study was the “standardized model of school duties,” which encompasses performance evaluation indicators and key components of quality education. Contextual conditions refer to environmental and socio-economic-cultural characteristics that affect school performance. Intervening conditions include barriers and limitations that may challenge the implementation of standardized school duties. Strategies consist of a set of actions designed to achieve the standardized model of school duties and to address anticipated barriers and limitations. Consequences represent the outcomes of the successful implementation of the standardized model of school duties and its associated strategies. Successful implementation of this model can enhance educational quality, reduce inequalities, and increase stakeholder satisfaction.